(untitled) (Fiep Bulletin - online, 2013)
Introduction: pedagogical practice of teacher must be planned and structured, contemplating objectives, contents and methodologies to promote qualitatively the process of teaching-learning. During classes of Practice of Formation II, the students related dissatisfaction with stages, especially those relating to pedagogical practice of teacher supervisor of stage. Objective: to investigate the pedagogical practice of teacher supervisor of stage about objectives, contents and class planning through perceptions of students. Methodology: this study presents descriptive characteristics with qualitative and quantitative approach. The population constituted in 50 academics from 8th period of Physical Education – degree – of Universidade Estadual de Montes Claros – Unimontes. The sample was composed by 40 academics. The instrument used was a structured questionnaire by authors from this research. The data collected were treated statistically by Software Statistical Package for the Social Science – SPSS – 18.0. Results: only 15% were capable to identify always the objectives proposed by teacher in each class, while 32% hardly identified the objectives. 42.5% succeeded to identify the content worked, with the predominating presence of sport with 67.5%; games and jokes were 30%; 2.5% identified the gymnastic; and no one related the work with Dance and Expressive Movements. Other datum that calls attention is the lack of methodological sequence between the contents developed from class to other, being that 47.5% related that hardly had this sequence and only 22.5% related that always was possible to identify the presence of planning of classes. Conclusion: a considerable percentage of professors of physical education has not developed a pedagogical practice supported in methodological principles and current conceptions of the same. The teachers do not plan their classes and do not work all contents proposed for physical education, limiting themselves to the sport.